Integrating COIL in teacher training: An estimation of learners´ motivational attitudes - Quintana-Ordorika, Amaia; Camino-Esturo, Edorta; Portillo-Berasaluce, Javier; Garay-Ruiz, Urtza (Frontiers in Education, 2023)
Collaborative Online International Learning experiences have gained territory in the last years, but the motivational impact they have on future Primary Education teachers in the field of teacher training education is to be researched. We present a quantitative study that tries to estimate the level of motivation of teacher training students that are in the trilingual degree in the Basque Country. This study examines the level of confidence, attention, satisfaction and relevance of learners in higher education according to Keller's ARCS model of motivation. It compares the results obtained between learners that have taken part in the Collaborative Online International Learning project, from now on COIL, and those that did not have the opportunity to take part in the virtual exchange and that had to develop the project in the traditional way. It also reflects the opinions they have regarding the general satisfaction of the project. The study involved 43 students from the UPV/EHU (University of the Basque Country) and students from Masaryk University. The data was collected through a validated questionnaire IMMS created in Google Forms. Key findings include that this faculty driven intervention that in all the dimensions, except Satisfaction, show significance results. Therefore, it is confirmed that the dimensions of Attention, Relevance, Confidence, as well as the overall score of the instrument (Global IMMS), show significant differences between the two groups analysed. The exceptionality of the Satisfaction dimension is very close to the rejection zone of the null hypothesis. This helps us to underline the positive value of the implementation of virtual exchanges and it is therefore concluded that the greater motivation, the higher the degree of positive attitudes towards taking part in virtual exchanges. These results allow decisions to be taken with regard to implementing these experiences in the initial training of teachers, since the data that has been collected has direct implications for global learning engagement level and as an effective pedagogical approach to prepare all students to cope with the requirements that a 21st century society has.